Outcome and complications after intra‐arterial thrombolysis for lower limb ischaemia with or without continuous heparin infusion. Issue 9 (25th June 2014) - Grip, O.; Kuoppala, M.; Acosta, S.; Wanhainen, A.; Åkeson, J.; Björck, M.
<x xml:space="preserve">Abstract</x> Background Thrombolysis is a common treatment for acute leg ischaemia. The purpose of this study was to evaluate different thrombolytic treatment strategies, and risk factors for complications. Methods This was a retrospective analysis of prospective databases from two vascular centres. One centre used a higher dose of heparin and recombinant tissue plasminogen activator (rtPA). Results Some 749 procedures in 644 patients of median age 73 years were studied; 353 (47·1 per cent) of the procedures were done in women. The aetiology of ischaemia was graft occlusion in 38·8 per cent, acute arterial thrombosis in 32·2 per cent, embolus in 22·3 per cent and popliteal aneurysm in 6·7 per cent. Concomitant heparin infusion was used in 63·2 per cent. The mean dose of rtPA administered was 21·0 mg, with a mean duration of 25·2 h. Technical success was achieved in 80·2 per cent. Major amputation and death within 30 days occurred in 13·1 and 4·4 per cent respectively. Bleeding complications occurred in 227 treatments (30·3 per cent). Blood transfusion was needed in 104 (13·9 per cent). Three patients (0·4 per cent of procedures) had intracranial bleeding; all were fatal. Amputation‐free survival was 83·6 per cent at 30 days at both centres. In multivariable analysis, preoperative severe ischaemia with motor deficit was the only independent risk factor for major bleeding (odds ratio (OR) 2·98; P <0·001). Independent risk factors for fasciotomy were severe ischaemia (OR 2·94) and centre (OR 6·50). Embolic occlusion was protective for major amputation at less than 30 days (OR 0·30; P = 0·003). Independent risk factors for death within 30 days were cerebrovascular disease (OR 3·82) and renal insufficiency (OR 3·86). Conclusion Both treatment strategies were successful in achieving revascularization with acceptable complication rates. Continuous heparin infusion during intra‐arterial thrombolysis appeared to offer no advantage.